H-solvability of the optimal control problem for a degenerate elliptic variational inequality - Zadoianchuk, N. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
We consider the optimal control problem for a degenerate elliptic variational inequality with weight function of potential type, which is in a differential operator. We prove the solvability of the optimal control problem in the class of the so-called H-admissible solutions. We justify the property of closureness for the set of H-admissible pairs in the product of topologies of the control space and the space of states.